Optimization of Industrial Machine Balancing Processes for Fastening Precision and Efficiency - Muhammad Ando Prasetyo; Yasinta Sindy Pramesti (Jurnal Indonesia Sosial Teknologi, 2024)
Balancing merupakan bagian sangat penting untuk proses yang digunakan Balancing is a very important part of the process used to adjust or balance equipment or mechanical components so that they operate stably and efficiently. Balancing machines are very important for maintaining optimal screw conveyor performance, and reducing screw conveyor noise or vibrations which can disrupt the quality of machine performance. This is one of the reasons for balancing the machine, it can experience vibrations which can cause a decrease in the quality of the machine's performance and also if left for a long period of time, these vibrations can damage other parts of the screw conveyor and cause excessive vibrations or unbalance of the machine. The balancing test method is using a HOFMAN HL-28 machine, in this test the screw conveyor tool is placed in the balancing machine then input data on the monitor with balancing parameters Rotor Wight: 1000.00 Kg, Balancing Test Speed: 149 RPM, Operation Speed: 300 RPM, Tolerance Plane 1 : 125,517, and Tolerance Plane 2 : 125,517 g. The results of the research obtained an initial unbalance left plan of 602 grams at an angle of 57.30, a right plan of 413 grams at an angle of 101.50, then the final unbalance was obtained for a left plan of 24 grams at an angle of 83.20, a right plan of 23 grams at an angle of 86.60. By conducting this research, it was found that the screw conveyor was suitable for use so that it could minimize vibration and damage to the screw motor.